Development of an alpha- and beta-imaging detector using a thin-stilbene plate for radon-222 progeny measurements. (January 2021) - Morishita, Yuki
Abstract: Radon-222 is a naturally-occurring radioactive gas, and the measurement of this isotope and its progeny is of interest from the viewpoint of protection against internal exposure. The author has developed a new alpha/beta-imaging detector combined with a waveform digitizer capable of imaging alpha- and beta-particle locations simultaneously. A 0.9-mm-thick stilbene plate was optically coupled to a position-sensitive photomultiplier tube (PSPMT), and the analog signals from the PSPMT were transferred in parallel to the waveform digitizer. For 5.5-MeV alpha particles, the detection efficiency was 97.2% for 2pi steradians, and the energy resolution of the 5.5 MeV alpha peak was 21.6 ± 0.18% full width at half maximum (FWHM). The imaging detector was able to discriminate between alpha and beta particles via the pulse-shape-discrimination (PSD) technique, as well as being capable of alpha- and beta-particle imaging. The imaging detector was used for 222 Rn-progeny measurements. When measuring the 222 Rn progeny, both 214 Bi and 214 Po are imaged simultaneously, and a correlation is found between the positions of 214 Bi and 214 Po. The developed detector will be useful as a 222 Rn detector and in alpha-continuous-air monitoring for nuclear facilities. Highlights: A new alpha/beta-imaging detector was developed using a 0.9-mm-thick stilbene plate, a waveform digitizer, and a position-sensitive photomultiplier tube (PSPMT). The developed imaging detector was capable of imaging alpha- and beta-particle locations simultaneously via the pulse-shape-discrimination (PSD) technique. The energy resolution of the 5.5 MeV alpha peak was 21.6 ± 0.18% FWHM. Both 214 Bi and 214 Po were imaged simultaneously, and a correlation was found between the positions of 214 Bi and 214 Po.